Antibodies in the Treatment of Haemophilia A—A Biochemical Perspective - Ferrière, Stephen; Lenting, Peter J. (Hämostaseologie, 2019)
Replacement therapy has been proven effective in the management of bleedings in haemophilia A. Nevertheless, this approach comes with several shortcomings, like the need for frequent intravenous infusions and the development of neutralizing antibodies in 20 to 30% of the patients with severe haemophilia A replacement. This has led to the development of novel strategies to expand the spectrum of treatment options, some of which are based on antibody technology. These include a bispecific antibody that bridges enzyme factor IXa and substrate factor X, monoclonal antibodies that block the function of tissue factor pathway inhibitor, and a factor VIII–nanobody fusion protein with strongly enhanced von Willebrand factor binding. In this review, functional and mechanistic considerations on the use of these antibody variants will be discussed.
Keywords: haemophilia; factor VIII; antibody